2018
DOI: 10.1021/acsaem.8b00238
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Fluorine Substitution and Thio-Alkylation on Photovoltaic Performances of Alternating Conjugated Polymers Based on Alkylthio-Substituted Benzothiadiazole-Quaterthiophene

Abstract: Three low bandgap polymers (PSDTBT-DFDT, PSDTfBT-DFDT, and PSDTffBT-DFDT) based on fluorine and alkylthio-substituted benzothiadiazole-quaterthiophene alternating units are synthesized and applied in polymer solar cells. The effects of fluorination and thio-alkylation on photophysical, electrochemical, and photovoltaic properties of the polymers are comparatively investigated. The results indicate that PSDTfBT-DFDT and PSDTffBT-DFDT show better light-harvesting abilities, lower HOMO energy levels, and better m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The same principle was then extended to different oligothiophenyl substrates, including oligothiophene, [129] bulk-heterojunction materials, [130] and conjugated polymers. [131] 4. Conclusions.…”
Section: Ebis Templating the Formation Of Porous Architecturementioning
confidence: 99%
“…The same principle was then extended to different oligothiophenyl substrates, including oligothiophene, [129] bulk-heterojunction materials, [130] and conjugated polymers. [131] 4. Conclusions.…”
Section: Ebis Templating the Formation Of Porous Architecturementioning
confidence: 99%
“…To enhance photovoltaic performances, the strategy of fluorine (F) substitution has been investigated in detail in polymer solar cells, and many reports have demonstrated that the fluorine atom, a strong electron-withdrawing group, can simultaneously downshift both the LUMO and HOMO energy levels [46][47][48][49][50][51] . In addition, benefiting from the smallest atomic radius and the strongest electronegativity in the halogen family, the introduction of fluorine atoms could improve the molecular absorption, increase intermolecular interaction, crystallinity as well as charge mobility, and obtain desired morphology [52][53][54][55] .…”
Section: Introductionmentioning
confidence: 99%
“…29 The homogeneous phase separation indicates good miscibility between PDFTB and ITIC, which contributes to exciton dissociation, charge separation and transport and promotes J SC of the devices. 18,30 The AFM and TEM images reveal that uorination on the polymer backbone can effectively promote the surface morphology and the miscibility between donor and acceptor simultaneously, which may be favorable for higher J SC .…”
Section: Charge Transport Propertiesmentioning
confidence: 99%